Heterogeneity of tumour mutational burden in metastatic NSCLC demonstrated by endobronchial ultrasound sampling - Leong, Tracy L.; Aloe, Christian; Aujla, Savreet; Wang, Hao; Gayevskiy, Velimir; Asselin-Labat, Marie-Liesse; Gray, Lesley-Ann; Steinfort, Daniel; Bozinovski, Steven (Frontiers in Oncology, 2023)
Introduction: Tumour mutational burden (TMB) is an important emerging biomarker for immune checkpoint inhibitors (ICI). The stability of TMB values across distinct EBUS tumour regions is not well defined in advanced lung cancer patients. Methods: This study included a whole-genome sequencing cohort (n=11, LxG cohort) and a targeted Oncomine TML panel cohort (n=10, SxD cohort), where paired primary and metastatic samples were obtained by endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA). Results: The LxG cohort displayed a strong correlation between the paired primary and metastatic sites, with a median TMB score of 7.70±5.39 and 8.31±5.88 respectively. Evaluation of the SxD cohort demonstrated greater inter-tumoural TMB heterogeneity, where Spearman correlation between the primary and metastatic sites fell short of significance. Whilst median TMB scores were not significantly different between the two sites, 3 out of 10 paired samples were discordant when using a TMB cut-off of 10 mutations per Mb. In addition, PD-L1 copy number and KRAS mutations were assessed, demonstrating the feasibility of performing multiple molecular tests relevant to ICI treatment using a single EBUS sample. We also observed good consistency in PD-L1 copy number and KRAS mutation, where cut-off estimates were consistent across the primary and metastatic sites. Conclusions: Assessment of TMB acquired by EBUS from multiple sites is highly feasible and has the potential to improve accuracy of TMB panels as a companion diagnostic test. We demonstrate similar TMB values across primary and metastatic sites, however 3 out of 10 samples displayed inter-tumoural heterogeneity that would alter clinical management.